Role of education after the COVID-19 pandemic fear: a multidisciplinary and scientific perspective - Naves-Barcelos, Monica (2020)
In response to the outbreak of the novel Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2), pathogen of the new coronavirus disease (COVID-19), several sectors and social activities have been affected, including education. At first, it is explained that educators and students can feel fragile during and after the SARS-CoV-2 outbreak. Subsequently, it is discussed that their relationship ought to be carefully established given the triggering of psychological and neuropsychiatric effects arising from neural coding and plasticity processes, which result in the formation of positive and negative memories in the short to long term. Finally, it is pointed out that the SARS-CoV-2 pandemic generates a need for adequacy and adaptation for the significant attention to students during the re-starting of studies, given that possible disorders of sensory modulation and involvement of limbic brain areas triggered in situations of risk of death, potential or real threat, can happen. It is assumed that at times of the SARS-CoV-2 pandemic, in addition to preserving life, one of the challenges is the behavioural (re)organisation, which includes habits from the educational context that need to contemplate a scientific perspective, seeking to transform the consequences of the pandemic fear on opportunities to reinforcement of familiar links. In the context of modern rationality, the SARS-CoV-2 pandemic is also a period to think about the relationship between scientific knowledge and common sense. With this logic, neurosciences can develop a new format for the teaching-learning process, so that educators and students experiencing the pandemic threatening do not manifest psychological distress and secondary consequences. Therefore, education can be considered a central space in decision-making in the face of SARS-CoV-2 pandemic. In this sense, the urgency of a multidisciplinary strategies development is highlighted, connecting the synergy between neurosciences and education after the COVID-19 pandemic.